Structure analysis of goose immunoglobulin Y Fc fragment - Jiang, Lei; Chang, Wei-Shan; Guo, Hao; Sun, Peng; Dai, Xiu-Mei (Central European Journal of Immunology, 2013)
Objective: Goose immunoglobulin Y (IgY)-Fc fragment gene is cloned. Material and methods : In order to obtain a certain length (106 bp) of constant domain gene, a pair of primer was designed according to the conserved nucleotide sequence of duck (CAA46322) and chicken (S00390) IgY-Fc fragment that was published by the GenBank. Special primers were designed by the Race method to amplify the 3' terminal cDNA. Results : Goose IgY heavy chain C domain partially unknown gene is successfully cloned, and it is 782bp. The full-length gene covers the Cν3 and Cν4 domains, i.e. Fc gene encoding 202 amino acids, the predicted molecular mass of Fc gene is 22.32 kDa. The deduced amino acid sequence of goose Fc showed 89.6% and 65.3% identity with those of duck and chicken, respectively. Conclusions : Conserved sequence amplification PCR combined with Race is effective in searching and isolating Fc gene of goose. It is successfully submitted to the GenBank; GenBank accession number is KC254644. The structure of goose IgY-Fc was analyzed using bioinformatics tools. In the 3D structure of goose IgY-Fc, the sequence identity is 64.29% to the template (chicken: 2w59A).